DAMPAK AKUNTABILITAS, TRANSPARANSI DAN PROFESIONALISME PAEDAGOGIK TERHADAP KINERJA GURU DI SMKN 21 JAKARTA - Sabrudin, Dadan; Suhendra, Euphrasia Suzy (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2019)
This study aims to determine the effect of accountability, transparency in budget management and pedagogical professionalism on teacher performance in Jakarta Vocational High School 21 Jakarta. The approach in this study is a descriptive and associative approach. The population in this study were teachers and employees of Vocational High School 21 Jakarta, which amounted to 50 people with sampling using census techniques. Data collection uses a questionnaire instrument with a Likert scale. The data analysis technique in this thesis uses quantitative descriptive method and multiple linear regression statistical analysis which is processed using SPSS version 20.0. The results of hypothesis testing prove that partially the accountability of school financial management variables have a significant effect on the performance of teachers at SMK 21 Jakarta. However, the transparency variable partially does not have a significant effect on the performance of teachers at SMK 21 Jakarta. While partially paedagogic professionalism variables have a significant effect on the performance of teachers of Vocational High School 21 Jakarta. Simultaneous hypothesis test results prove that accountability, transparency and professionalism have a significant effect on the performance of teachers at SMK 21 Jakarta. The magnitude of the influence of accountability and transparency and professionalism of teachers on teacher performance is 49.2%. This means that 49.2% changes in the performance of teachers at Vocational High School 21 Jakarta can be explained by variables of accountability and transparency and professionalism, while the remaining 50.8% is influenced by other factors.